Asymmetry of Taxes and Subsidies in Regulating Stochastic Mishap - Just, Richard E.; Zilberman, David (Quarterly Journal of Economics, 1979)
I. The model 140.—II. Marginal effects of taxes and subsidies, 142.—III. The role of risk preferences, 143.—IV. Relative effectiveness of taxes and subsidies, 145.—V. Conclusions, 147.